WTAP regulates autophagy in colon cancer cells by inhibiting FLNA through N6-methyladenosine. Issue 1 (31st December 2023) - Huang, Liang; Shao, Jinfan; Xu, Xijuan; Hong, Weiwen; Yu, Wenfeng; Zheng, Shuang; Ge, Xiaogang
ABSTRACT: Our study investigated the role of WTAP in colon cancer. We employed experiments including m6A dot blot hybridization, methylated RNA immunoprecipitation, dual-luciferase, and RNA immunoprecipitation to investigate the regulatory mechanism of WTAP. Western blot was performed to analyze the expression of WTAP, FLNA and autophagy-related proteins in cells. Our results confirmed the up-regulation of WTAP in colon cancer and its promoting effect on proliferation and inhibiting effect on apoptosis. FLNA was the downstream gene of WTAP and WTAP-regulated m6A modification led to post-transcriptional repression of FLNA. The rescue experiments showed that WTAP/FLNA could inhibit autophagy. WTAP-mediated m6A modification was confirmed to be crucial in colon cancer development, providing new insights into colon cancer therapy.